Methodology to Validate Results from European Research Projects: The C2NET Case Study - R. Sanchis; B. Andrés; R. Poler (International Journal of Production Management and Engineering, 2019)
One of the main priorities of the European Commission is the utilisation of European Projects results in further research activities, or in developing, creating and marketing a product or process. For this reason, it is critical to test and validate European projects results before implementing them in real scenarios. In this paper, a general validation methodology addressed to the assessment of technological results has been defined. This general methodology offers the foundations to define specific validation methodologies to validate particular results of different Research Projects. As an example, the general methodology has been applied to define a specific one for the validation of an Optimiser developed within the European Research Project: Cloud Collaborative Manufacturing Networks (C2NET) to guarantee the proper operation of the research results and facilitate their later real implementation and exploitation.